Use of whole-exome sequencing to identify novel monogenic gene mutations and genotype–phenotype correlations in Chinese Han children with urolithiasis - Wang, Zhi; He, Tianqu; liu, Li; Tong, Fangyun; Li, Chuangye; Zhao, Yaowang; Li, Yanfang (Frontiers in Genetics, 2023)
Recently, there is an increasing trend on incidence of urolithiasis (UL) in children. Although the pathogenesis of pediatric UL is controversial and remains unclear, multiple monogenic causes of UL have been identified. We aim to investigate the prevalence of inherited UL causes and explore the genotype-phenotype correlation in Chinese pediatric group. In this study, we analyzed the DNA of 82 pediatric UL patients using exome sequencing (ES). The data of metabolic evaluation and genomic sequencing were subsequently analyzed together. We detected 54 genetic mutations in 12 of 30 UL-related genes. Fifteen detected variants were described as pathogenic mutations, twelve mutations were considered as likely pathogenic. Molecular diagnoses were made in 21 patients with pathogenic or likely pathogenic variants. Eleven novel mutations that were previously reported were identified in this cohort. Hyperoxaluria-related mutations were detected in 88.9% cases (8/9) with calcium oxalate stone, while cystinuria-causing defects were found in 80% individuals (4/5) diagnosed with cystine stone. Our study highlights the significant genetic abnormality in pediatric UL and demonstrates the diagnostic power of ES for the screening of patients with UL.